Promoting creative thinking for gifted students in undergraduate mathematics - Ngiamsunthorn, Parinya Sa (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Gifted students need a form of special education through extracurricular and learning experiences because they have extraordinary potential in terms of intelligence, creativity, social and mentality, compared to other students. This study aims to investigate various teaching and learning approaches designed for gifted students, and to constitute appropriate techniques that enhance their creative thinking in mathematics. The participants of this study were first-year gifted students enrolled in fundamental mathematics courses towards their undergraduate engineering programs at a science and technology-based university in Thailand. This study discovered that an adequate use of challenge-based learning, problem solving process, project-based learning, well-designed questions and in-depth learning style in the classroom effectively fostered their insightful and creative thought. Moreover, an online tool such as Facebook could be used as a learning platform outside the classroom to engage them in online discussion and collaboration and to challenge their thinking. Ultimately, based on students’ feedbacks and evaluation, this study found that a combination of these techniques and methods built up a more comfortable and motivating atmosphere that helped them for creative thinking and corresponded to their needs and satisfaction.